2020
DOI: 10.3390/pathogens10010015
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin for the Treatment of Helicobacter pylori Infection: A Review

Abstract: Nowadays, apart from having to know first-line Helicobacter pylori eradication regimens well, we must also be prepared to face treatment failures. The aim of this review is to summarize the role of rifabutin in the management of H. pylori infection. Bibliographical searches were performed in PubMed. Data on resistance and efficacy of rifabutin-containing regimens on H. pylori eradication were meta-analyzed. Mean H. pylori rifabutin resistance rate (39 studies, including 9721 patients) was 0.13%; when studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
71
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 129 publications
(248 reference statements)
5
71
0
3
Order By: Relevance
“…Rifabutin is stable at a pH range of 2-8 and is not readily destroyed by stomach acid [14]. A recent review of 39 studies (9721 patients) concluded a resistance rate to rifabutin of < 1.0% (0.13%), and this rate fell to 0.07% in treatment-naïve patients [7]. Because H. pylori regimens are largely prescribed empirically, rifabutin-triple therapy (RHB-105) can be prescribed without concern for resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Rifabutin is stable at a pH range of 2-8 and is not readily destroyed by stomach acid [14]. A recent review of 39 studies (9721 patients) concluded a resistance rate to rifabutin of < 1.0% (0.13%), and this rate fell to 0.07% in treatment-naïve patients [7]. Because H. pylori regimens are largely prescribed empirically, rifabutin-triple therapy (RHB-105) can be prescribed without concern for resistance.…”
Section: Discussionmentioning
confidence: 99%
“…After failure of a third-line treatment, a fourth-line with rifabutin is generally recommended [ 7 ]. However, in the largest multi-centre study including this antibiotic, an eradication rate of 52% was reported [ 27 ], although a recent review reported an eradication rate of 73% [ 9 ]. All our patients had previously received (and failed) rifabutin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, H. pylori infection persists even after multiple eradication treatments. High-dose proton pump inhibitor–amoxicillin dual regimens or rifabutin-based therapies have generally been recommended for patients with several previous eradication failures [ 9 , 10 ], but these regimens also fail in some cases. It should be noted that these hyper-refractory cases are an extremely rare exception, with less than 1% of patients remaining infected with H. pylori after multiple (>4–5) eradication treatments [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-Asian participants were evaluated based on the CYP2C19 genotype and there were no concerns with respect to safety or efficacy in poor metabolizing participants. Rifabutin has been used successfully for H pylori in Asians (Japan, Korea, and China), 4 and their exclusion in the trial should not be considered a reason not to use it in Asians. A second issue regarding rifabutin was that serious adverse reactions may occur, such as myelosuppression.…”
mentioning
confidence: 99%
“…for H pylori treatment) and the emergence of rifabutin resistant TB. 4 Rifabutin is indicated for Mycobacterium avian intracellulare (MAI), which is an atypical bacterium and a rare disease associated with HIV-infected and immunocompromised hosts. Importantly, rifabutin is not a first line treatment for Mycobacterium tuberculosis (TB), but rather, is reserved for patients who cannot tolerate rifampicin or those with concerns of potential drug–drug interactions.…”
mentioning
confidence: 99%